Occidente, canon y literatura hispanoamericana - Dante Liano (Caravelle)
This article proposes the following idea: that, with what is known as the «boom», the Spanish American literature entirely joined modernity (at least, in the case of modern publishing industry’s devices) and also became a member of western canon. The first consequence was the recognition that behind the «boom» writers there was a solid tradition whose authors had created an important literature. The second one, was that such a tradition continued thanks to those authors who followed García Márquez and Co.: beginning with Cabrera Infante, then Puig and also Roberto Bolaño. The article ends with the guesswork that there are three canons for Latin American litterature, which don’t necesarily coincide: the Spanish canon, the North American academic one, the internal canon.